2022
DOI: 10.1051/0004-6361/202243454
|View full text |Cite
|
Sign up to set email alerts
|

Three new brown dwarfs and a massive hot Jupiter revealed by TESS around early-type stars

Abstract: Context. The detection and characterization of exoplanets and brown dwarfs around massive AF-type stars is essential to investigate and constrain the impact of stellar mass on planet properties. However, such targets are still poorly explored in radial velocity (RV) surveys because they only feature a small number of stellar lines and those are usually broadened and blended by stellar rotation as well as stellar jitter. As a result, the available information about the formation and evolution of planets and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 177 publications
0
6
0
Order By: Relevance
“…HIP 33609 b joins a population of 37 transiting BDs published to date (Grieves et al 2021;Carmichael et al 2022;Psaridi et al 2022;Sebastian et al 2022), and is one of the most extreme substellar companions yet discovered. HIP 33609 not only has a precise age measurement of 150 ± 25 Myr, but is also the brightest and hottest host of a transiting BD discovered to date.…”
Section: Discussionmentioning
confidence: 96%
“…HIP 33609 b joins a population of 37 transiting BDs published to date (Grieves et al 2021;Carmichael et al 2022;Psaridi et al 2022;Sebastian et al 2022), and is one of the most extreme substellar companions yet discovered. HIP 33609 not only has a precise age measurement of 150 ± 25 Myr, but is also the brightest and hottest host of a transiting BD discovered to date.…”
Section: Discussionmentioning
confidence: 96%
“…We have confirmed and characterized 20 new short-period giant planets detected by the TESS mission, based on extensive ground-based photometric, spectroscopic, and imaging observations. These objects join a host of other giant planets that have been discovered by TESS over the last few years (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Psaridi et al 2022;Rodriguez et al 2022;Yee et al 2022), showcasing how TESS is rapidly transforming our knowledge of hot Jupiters by providing a uniform, all-sky sample of these planets. Yee et al (2021) found that the sample of known transiting hot Jupiters was only ∼40% complete at a magnitude-limit of G < 12.5.…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed and characterized twenty new short-period giant planets detected by the TESS mission, based on extensive ground-based photometric, spectroscopic, and imaging observations. These objects join a host of other giant planets that have been discovered by TESS over the last few years (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Rodriguez et al 2022;Psaridi et al 2022;Yee et al 2022), showcasing how TESS is rapidly transforming our knowledge of hot Jupiters by providing a uniform, all-sky sample of these planets. Yee et al (2021) found that the sample of known transiting hot Jupiters was only ∼ 40% complete at a magnitude-limit of G < 12.5.…”
Section: Discussionmentioning
confidence: 99%